The Effect of Medium and Culture Date on Big Roll Production - مازن نصور,; نيرمين أحمد , (Latakia University Journal -Biological Sciences Series, 2023)
The aim of this research is to determine the best date and culture medium for the production of big rolls consisting of seed mixture (Lolium perenne, Festuca Arundinacea, Festuca rubra, Poa partensis) with the lowest costs. Seven different mediums were experimented in two different culture dates (15 September and 1 April). The results showed that the mediums consisting of turf or spent mushrooms compost gave the best germination rate (78-84%) in the two culture dates. They also gave ready big rolls in a period of time less than in the other mediums (78-102 days). The mediums also gave the best quality of big rolls in terms of light weight (41.96- 53.89 kg/m2), coverage rate (93-98%), and color. The medium that consisted of spent mushroom compost achieved an economic increase higher than that in the other mediums, where the coefficient of profitability in the former was (194.4%).